2022
DOI: 10.1371/journal.pone.0267193
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of G6PD diagnostic test for Plasmodium vivax radical cure in Lao PDR: An economic modelling study

Abstract: Background Plasmodium vivax (Pv) infections were 68% of the total malaria burden in Laos in 2019. The parasite causes frequent relapses, which can be prevented by primaquine (PMQ). Testing for glucose-6-phosphate-dehydrogenase (G6PD) deficiency is recommended before giving PMQ to avoid haemolysis. Because of the risk of haemolysis in G6PD intermediate deficiencies among females, Laos uses the PMQ 14-days regimen only in G6PD normal females. Among G6PD point-of-care tests, qualitative tests cannot differentiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…One recent usability study conducted among intended test users from three high malaria burden settings found that, with appropriate training, the test can be used in clinics managing malaria cases [42]. Recent studies also suggest that the incorporation of the test into P. vivax case management in Brazil and Laos is cost effective; however, factors such as clinic case burdens and G6PD deficiency prevalence are important considerations [43,44]. Together, these performance, usability, and cost-effectiveness findings suggest that the STANDARD G6PD Test can be used in malaria endemic settings to support G6PD classification and significantly reduce the risk of drug induced hemolysis when prescribing primaquine or tafenoquine, as well as other drugs such as rasburicase [45].…”
Section: Implications For Malaria Programs and Future Researchmentioning
confidence: 99%
“…One recent usability study conducted among intended test users from three high malaria burden settings found that, with appropriate training, the test can be used in clinics managing malaria cases [42]. Recent studies also suggest that the incorporation of the test into P. vivax case management in Brazil and Laos is cost effective; however, factors such as clinic case burdens and G6PD deficiency prevalence are important considerations [43,44]. Together, these performance, usability, and cost-effectiveness findings suggest that the STANDARD G6PD Test can be used in malaria endemic settings to support G6PD classification and significantly reduce the risk of drug induced hemolysis when prescribing primaquine or tafenoquine, as well as other drugs such as rasburicase [45].…”
Section: Implications For Malaria Programs and Future Researchmentioning
confidence: 99%
“…However, as the study progressed, proficiency scores declined and more HCPs failed the test, further reinforcing the need for ongoing training and supervision. User acceptability as well as proficiency for the STANDARD G6PD test has also been demonstrated in multiple settings across multiple end users [ 16 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study did not investigate cost effectiveness of inclusion of G6PD testing. This has been investigated in settings with higher P. vivax caseloads where inclusion of G6PD testing was shown to be cost effective [ 22 , 23 , 24 ]. With the low case load in Vietnam, cost effectiveness is much harder to demonstrate and the overall costs for the intervention in context of overall malaria program costs are likely to be more critical.…”
Section: Discussionmentioning
confidence: 99%
“…41 Recent studies also suggest that the incorporation of the test into P. vivax case management in Brazil and Laos is cost effective; however, factors such as clinic case burdens and G6PD deficiency prevalence are important considerations. 42,43 Together, these performance, usability, and costeffectiveness findings suggest that the STANDARD G6PD Test can be used in malaria endemic settings to support G6PD classification and significantly reduce the risk of drug induced hemolysis when prescribing primaquine or tafenoquine, as well as other drugs such as rasburicase. 44 However, the positive predictive power of the test among this population, where a significant proportion of individuals classified as G6PD deficient by the STANDARD test are in fact normal represents an operational challenge in settings where confirmatory testing cannot be conducted.…”
Section: Implications For Malaria Programs and Future Researchmentioning
confidence: 96%